Reintroduce Thalidomide? (B) - Diermeier, Daniel; Hermitage, Jason; Thaker, Shail; Heinze, Justin (London : Kellogg School of Management, 2006)
The case explains how and why Thalidomide was at last licensed by the FDA and how this would benefit the manufacturer of the drug Celgene.
Originally published in Diermeier, D., Hermitage, J., Thaker, S., & Heinze, J. (2006). Reintroduce thalidomide? (B). 5-104-003(B). Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; United States. -- Food and Drug Administration; Immunopharmacology; Thalidomide